2017
DOI: 10.1097/igc.0000000000001079
|View full text |Cite
|
Sign up to set email alerts
|

Time Trends in the Incidence and Mortality of Ovarian Cancer in Ireland, Northern Ireland, and Israel, 1994–2013

Abstract: Time trends in ovarian cancer incidence (decreasing) and mortality (decreasing) were similar in Ireland, NI, and Israeli Jews, following global trends, with a more prominent incidence decline in Israeli Jews. Decreasing mortality trends are driven by falling incidence in the countries studied rather than improved survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
2
5
0
Order By: Relevance
“…We observed modest decrease in ovarian cancer mortality rates in Lithuania. Results are in line with those reported in previous studies, where decreasing rates were observed [ 2 , 11 , 20 , 21 ]. Significant period effect, detected in our study, indicates improvements in diagnosis or treatment of ovarian cancer.…”
Section: Discussionsupporting
confidence: 93%
“…We observed modest decrease in ovarian cancer mortality rates in Lithuania. Results are in line with those reported in previous studies, where decreasing rates were observed [ 2 , 11 , 20 , 21 ]. Significant period effect, detected in our study, indicates improvements in diagnosis or treatment of ovarian cancer.…”
Section: Discussionsupporting
confidence: 93%
“… 24 However, there was a reduction in cancer incidence in Israeli Jews and the Philippines. 25 , 26 There were several reasons for explaining the increasing incidence trends in Korea and Japan. Over diagnosis of some cancers (like thyroid cancer) could one reason for the increasing trend of cancer incidence, especially in Korea.…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian cancer is a cosmopolitan disease as it occurs in every geographical location and in every race [1,30]. Epithelial ovarian cancer is the commonest subtype all around the world with high-grade serous accounting for 60-85% of cases [22,[35][36][37][38].…”
Section: Racial and Geographical Riskmentioning
confidence: 99%
“…Recent statistics from the US show a decline in incidence from 16.6/100,000 in 1985 to 11.8/100,000 in 2018 [39]. Incidence is also high in New Zealand and among Jewish women in Israel but low in Africa and Asia with estimated rates of <3/100,000 [37]. Japan, though reported to have low incidence is experiencing a rising trend in the disease of recent [40].…”
Section: Racial and Geographical Riskmentioning
confidence: 99%